Examining the relationship between language development, executive function, and screen time: A systematic review. - Mazhar Bal; Ayşe Gül Kara Aydemir; Gülüzar Şule Tepetaş Cengiz; Ahmet Altındağ (PLoS ONE)
This systematic review study examines the relationship between language development, executive function, and screen time in early childhood. The early childhood period is a crucial phase for the development of the brain, during which fundamental language and executive function skills undergo rapid evolution. This review synthesizes findings from 14 peer-reviewed studies that focused on language development, executive function, and screen time together to provide a comprehensive understanding of their relationship. The findings of current study were categorized under four themes: screen content and adherence to guidelines, parent-child interaction and the family context, passive and active screen time, and attention issues. The findings suggest that interactive and educational screen content may positively influence language development and executive functions when aligned with recommended screen time guidelines. In contrast, excessive passive screen time, such as watching television, has been associated with negative impacts on cognitive and social skills, particularly affecting attention, memory, and emotional regulation. The prevalence of attention problems is found to be higher in individuals who engage in high levels of screen time. This highlights the necessity for balanced consumption of screen media. The review emphasizes the pivotal role of parent-child interaction, where high-quality engagement and verbal scaffolding during screen time can mitigate adverse effects. Furthermore, socioeconomic and cultural factors also play a significant role. Higher socioeconomic status (SES) families are better able to manage screen time and leverage educational content to support development. These findings have the potential to inform the actions of parents, educators, and policymakers. Adherence to recommended screen time guidelines can mitigate the potential negative impact on executive functions and language skills. Furthermore, the importance of limiting passive screen time and ensuring a balance between screen use and real-world interactions and play opportunities is also highlighted.